Flow cytometry-based biomarker assay for in vitro identification of microalgal symbionts conferring heat tolerance on corals - Buerger, Patrick; Buler, Marcin; Yeap, Heng L.; Edwards, Owain R.; van Oppen, Madeleine J. H.; Oakeshott, John G.; Court, Leon (Frontiers in Marine Science, 2023)
Corals’ tolerance to high temperature stress largely depends on their symbiotic microalgae (Symbiodiniaceae). However, the contributing microalgal traits and their relationships to one another are largely unclear. Here we compare the in vitro cellular profiles of seven Cladocopium C1acro microalgal strains (derived from the same ancestral strain) during a four-week exposure to 27°C or 31°C. One was an unselected wild-type strain (WT), three were selected at 31°C for nine years and shown to confer thermal tolerance on the coral host (SS+) and three others were similarly selected but did not confer tolerance (SS-). Flow cytometry was used to measure the staining intensities of cells treated with dyes representing the intracellular stress indicators reactive oxygen species (ROS), reduced glutathione (rGSH) and mitochondrial activity, as well as cell size/shape and photosynthetic pigments. Cell densities and photosynthetic efficiency (ϕPSII, Fv/Fm) were also measured. WT showed the highest levels of intracellular ROS and mitochondrial activity, lowest rGSH and largest cell sizes at both temperatures. SS+ strains had the lowest ROS and highest rGSH values and a unique pattern of correlations among parameters at 31°C. Our results support previous reports implicating the role of microalgal ROS, mitochondria and rGSH in holobiont thermal tolerance and suggest flow cytometry is a useful pre-screening tool for identifying microalgal strains with enhanced thermal tolerance.